UNLOCKING VOCABULARY THROUGH MOVEMENT: ASSESSING THE IMPACT OF TOTAL PHYSICAL RESPONSE (TPR) ON WORD RETENTION - Shahina Shukhratova (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Vocabulary acquisition is a fundamental component of second language learning, but retaining new vocabulary remains a persistent challenge for learners. Total Physical Response (TPR), a language teaching method developed by James Asher, aims to enhance language retention by pairing verbal input with physical movement. This study investigates the effectiveness of TPR in improving vocabulary retention among English as a Foreign Language (EFL) learners. A quasi-experimental design was used, involving two groups of intermediate-level students: one instructed using traditional methods and the other through TPR. Both immediate and delayed post-tests were administered to evaluate vocabulary retention. The results revealed that students in the TPR group retained significantly more vocabulary than those in the control group, supporting the hypothesis that movement-based instruction can enhance memory and recall in language learning. The study also identifies key methodological aspects crucial for implementing TPR effectively in classroom contexts.